Subjective response to antipsychotic treatment and compliance in schizophrenia. A naturalistic study comparing olanzapine, risperidone and haloperidol (EFESO Study) - García-Cabeza, Ignacio (BioMed Central, 2001)
BACKGROUND: In order to compare the effectiveness of different antipsychotic drugs in the treatment of schizophrenia it is very important to evaluate subjective response and compliance in patient cohorts treated according to routine clinical practice. METHOD: Outpatients with schizophrenia entered this prospective, naturalistic study when they received a new prescription for an antipsychotic drug. Treatment assignment was based on purely clinical criteria, as the study did not include any experimental intervention. Patients treated with olanzapine, risperidone or haloperidol were included in the analysis. Subjective response was measured using the 10-item version of the Drug Attitude Inventory (DAI-10), and treatment compliance was measured using a physician-rated 4 point categorical scale. RESULTS: A total of 2128 patients initiated treatment (as monotherapy) with olanzapine, 417 with risperidone, and 112 with haloperidol. Olanzapine-treated patients had significantly higher DAI-10 scores and significantly better treatment compliance compared to both risperidone- and haloperidol-treated patients. Risperidone-treated patients had a significantly higher DAI-10 score compared to haloperidol-treated patients. CONCLUSION: Subjective response and compliance were superior in olanzapine-treated patients, compared to patients treated with risperidone and haloperidol, in routine clinical practice. Differences in subjective response were explained largely, but not completely, by differences in incidence of EPS.